2019
DOI: 10.1088/1755-1315/370/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of gregarine parasitism of wild marine bivalve, Anadara cornea (reeve, 1844) concerning seasonality and water quality

Abstract: Gregarines are groups of protozoan parasites that ubiquitously infect arthropods worldwide including host from terrestrial and aquatic environment. To date, 1,600 gregarine species have been described, but less study for invertebrates have been recorded for these apicomplexan parasites. Wild marine bivalve species Anadara cornea (Reeve, 1844) populations were surveyed for gregarines at Setiu Lagoon in Terengganu, Malaysia for a year. This species of bivalve was previously unlisted as hosts. Malaysia is known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This study by monthly sampling revealed some differences in the seasonal prevalence of the parasite in bivalves, Anadara cornea (Reeve, 1844). A previous study reported that the prevalence of the gregarine genus Nematopsis in Donax faba, Meretrix meretrix and Saccostrea cucullata was negative from November 2000 to November 2001 [3]. Meanwhile, Chakraborti and Bandyopadhyay (2010) described a new species of the genus Nematopsis from tiger prawns of Sundarbans [15].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This study by monthly sampling revealed some differences in the seasonal prevalence of the parasite in bivalves, Anadara cornea (Reeve, 1844). A previous study reported that the prevalence of the gregarine genus Nematopsis in Donax faba, Meretrix meretrix and Saccostrea cucullata was negative from November 2000 to November 2001 [3]. Meanwhile, Chakraborti and Bandyopadhyay (2010) described a new species of the genus Nematopsis from tiger prawns of Sundarbans [15].…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the samples were collected from Setiu lagoon (at 05 o 40' 58.6" N and 102 o 42' 44.5" E) by using catching wire rope or "Tangguk Dawai". According to the previous report, the gills and digestive tract of the bivalve are specifically chosen as the target organs of infection [3]. The A. cornea (Reeve, 1844) samples were measured for their weight and length.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…are the most abundant group of fauna observed from seagrass meadows in Malaysia, where the artificial seagrass meadows in east Malaysia recorded the highest number of fish species. Other faunal studies, for example, epibenthic dinoflagellates [41], bivalves[26, 49, 50,97,129,133,137,140,[161][162][163][164][165], gastropods[26, 52,97,108,120,123,125,136,166], benthic community [26,96,127,140,141,[167][168][169][170], amphipods[51,126,171], shrimp…”
mentioning
confidence: 99%